2019
DOI: 10.1111/jvim.15549
|View full text |Cite
|
Sign up to set email alerts
|

The use of focused cardiac ultrasound to screen for occult heart disease in asymptomatic cats

Abstract: Background Focused cardiac ultrasound (FCU) helps detect occult heart disease in human patients. Hypothesis Focused cardiac ultrasound by a nonspecialist practitioner (NSP) will increase the detection of occult heart disease in asymptomatic cats compared with physical examination and ECG. Animals Three hundred forty‐three client‐owned cats: 54 excluded and 289 analyzed. Methods Multicenter prospective cohort study. Twenty‐two NSPs were trained to perform FCU. Cats without clinical signs of heart disease were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Fortunately, with regard to therapeutic decision‐making, the requirement for diuretics in cats with CHF and the approach to management of ATE are similar regardless of the form of cardiomyopathy. A basic level of echocardiographic skill (eg, ability to detect moderate to severe left atrial enlargement) can be sufficient to identify the more advanced stages of cardiomyopathy . Other diagnostic tests may facilitate disease staging, identification of important comorbidities and establishing prognosis.…”
Section: Diagnosismentioning
confidence: 99%
“…Fortunately, with regard to therapeutic decision‐making, the requirement for diuretics in cats with CHF and the approach to management of ATE are similar regardless of the form of cardiomyopathy. A basic level of echocardiographic skill (eg, ability to detect moderate to severe left atrial enlargement) can be sufficient to identify the more advanced stages of cardiomyopathy . Other diagnostic tests may facilitate disease staging, identification of important comorbidities and establishing prognosis.…”
Section: Diagnosismentioning
confidence: 99%
“…Advanced analysis of the geometry of the mitral valve by 3‐dimensional (3D) echocardiography also expands our understanding of the disease phenotype . Although advanced 3D echocardiography is limited primarily to research centers, point‐of‐care ultrasound was demonstrated to be a useful screening tool to overcome the challenges of detecting heart disease in cats by nonspecialists practitioners . The last 5 years also demonstrate an increased focus on the right ventricle, the side of the heart that has been largely ignored in the past.…”
mentioning
confidence: 99%
“…12 Although advanced 3D echocardiography is limited primarily to research centers, point-of-care ultrasound was demonstrated to be a useful screening tool to overcome the challenges of detecting heart disease in cats by nonspecialists practitioners. 13 The last 5 years also demonstrate an increased focus on the right ventricle, [14][15][16] the side of the heart that has been largely ignored in the past. Further focus on the right ventricle has sought to improve our understanding of the utility of echocardiography to estimate pulmonary arterial pressure and enhanced our appreciation of pulmonary hypertension as a cause of morbidity in animals.…”
mentioning
confidence: 99%
“…Advanced analysis of the geometry of the mitral valve by three‐dimensional echocardiography also expands our understanding of the disease phenotype . While advanced three‐dimensional echocardiography is limited primarily to research centers, point‐of‐care ultrasound was demonstrated to be a useful screening tool to overcome the challenges of detecting heart disease in cats by non‐specialists practitioners . The past 5 years also demonstrate an increased focus on the right ventricle, the side of the heart that has been largely ignored in the past.…”
mentioning
confidence: 99%
“…12 While advanced three-dimensional echocardiography is limited primarily to research centers, point-of-care ultrasound was demonstrated to be a useful screening tool to overcome the challenges of detecting heart disease in cats by non-specialists practitioners. 13 The past 5 years also demonstrate an increased focus on the right ventricle, [14][15][16] the side of the heart that has been largely ignored in the past. Further focus on the right ventricle has sought to improve our understanding of the utility of echocardiography to estimate pulmonary arterial pressure and enhanced our appreciation of pulmonary hypertension as a cause of morbidity in animals.…”
mentioning
confidence: 99%